The anticancer potential of tetrahydrocurcumin-phytosomes against oral carcinoma progression - Nehal Raouf; Zeinab Elsayed Darwish; Omneya Ramadan; Hebatallah S. Barakat; Shimaa A. Elbanna; Marwa M. Essawy (BMC, 2024)
Abstract Background Herbal medicine combined with nanotechnology offers an alternative to the increasing burden of surgery and/or chemotherapy, the main therapeutics of oral carcinoma. Phytosomes are nano-vesicular systems formed by the interaction between phospholipids and phyto-active components via hydrogen bonding, exhibiting superior efficacy over pure phytocomponents in drug delivery. Methods Tetrahydrocurcumin (THC)-phytosomes were prepared by thin film hydration method. After characterization, in vitro cytotoxicity, antiproliferative capacity, antioxidant potential and full apoptotic workup were paneled on oral squamous cell carcinoma (SCC4) in comparison with native THC-solution and cisplatin (3.58 µg/mL intravenous injection), as positive controls. In addition, we tested the three medications on normal oral keratinocytes and gingival fibroblasts to attest to their tissue-selectivity. Results Successful preparation of THC-phytosomes using 1:1 molar ratio of THC to phospholipid exhibited significantly increased aqueous solubility, good colloidal properties, and complete drug release after one hour. On SCC4 cells, THC-phytosomes, at their dose-/time-dependency at ~ 60.06 µg/mL escalated cell percentages in the S-phase with 32.5 ± 6.22% increase, as well as a startling 29.69 ± 2.3% increase in apoptotic population. Depletion of the cell colonies survival to 0.29 ± 0.1% together with restraining the migratory rate by -6.4 ± 6.8% validated THC-phytosomes' antiproliferative capacity. Comparatively, the corresponding results of THC-solution and cisplatin revealed 12.9 ± 0.9% and 25.8 ± 1.1% for apoptosis and 0.9 ± 0.1% and 0.7 ± 0.08% for colony survival fraction, respectively. Furthermore, the nanoformulation exhibited the strongest immuno-positivity to caspase-3, which positively correlated with intense mitochondrial fluorescence by Mitotracker Red, suggesting its implication in the mitochondrial pathway of apoptosis, a finding further explained by the enormously high Bax and caspase-8 expression by RT-qPCR. Finally, the THC groups showed the lowest oxidative stress index, marking their highest free radical-scavenging potential among the test groups. Conclusions THC-phytosomes are depicted to be an efficient nanoformulation that enhanced the anticancer efficacy over the free drug counterpart and the conventional chemotherapeutic. Additionally, being selective to cancer cells and less cytotoxic to normal cells makes THC-phytosomes a potential candidate for tissue-targeted therapy.